2015
DOI: 10.1073/pnas.1505063112
|View full text |Cite
|
Sign up to set email alerts
|

Self-control forecasts better psychosocial outcomes but faster epigenetic aging in low-SES youth

Abstract: There are persistent socioeconomic disparities in many aspects of child development in America. Relative to their affluent peers, children of low socioeconomic status (SES) complete fewer years of education, have a higher prevalence of health problems, and are convicted of more criminal offenses. Based on research indicating that low self-control underlies some of these disparities, policymakers have begun incorporating character-skills training into school curricula and social services. However, emerging data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
154
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(177 citation statements)
references
References 43 publications
22
154
0
1
Order By: Relevance
“…The majority of findings presented by Miller et al (3) replicate previous studies showing benefits of self-control. In a sample of low-SES, African-American high school students in a rural area, those with greater self-control had greater reductions in psychosocial problems including depression, internalizing symptoms, aggressive behavior, and substance abuse.…”
Section: Self-regulation and Healthsupporting
confidence: 78%
“…The majority of findings presented by Miller et al (3) replicate previous studies showing benefits of self-control. In a sample of low-SES, African-American high school students in a rural area, those with greater self-control had greater reductions in psychosocial problems including depression, internalizing symptoms, aggressive behavior, and substance abuse.…”
Section: Self-regulation and Healthsupporting
confidence: 78%
“…Socioeconomic status has been identified as one of the most important health determinants throughout the life course (Miller et al 2015). Low financial resources and all the other exposures that go along with poverty -poor schools, chaotic families, exposure to violence, and victimization -limit opportunities for growth or acquisition of other resources that enhance quality of life (Wadsworth et al 2016;Kim et al 2015).…”
Section: Childhood Socioeconomic Statusmentioning
confidence: 99%
“…Similarly, many potential powerful positive influences can occur during this period in life (e.g., marriage, educational achievement, mentoring) that can enhance the developmental and mental health trajectory. Therefore, experiences both distal (early childhood) and proximal (during emerging adulthood) can influence, either positively or negatively, the developmental and mental health trajectory of the emerging adult (Miller et al 2015). Practical supports during EA provided by families include financial support for education, transportation, independent living, health insurance, and other necessities.…”
Section: Protective and Risk Factors That Impact Emerging Adulthoodmentioning
confidence: 99%
“…Nevertheless, better psychological functioning may not be uniformly related to better physical health status in all populations, even at low levels of SES. For example, a recent study reported that greater self-control was associated with a marker of faster epigenetic aging in rural African-American youth (Miller, Yu, Chen, & Brody, 2015). …”
mentioning
confidence: 99%